Shape from texture: homogeneity revisited - Criminisi, Antonio; Zisserman, Andrew (Proc. British Machine Vision Conference (BMVC), 2000)
The objective of this paper is to estimate the orientation of a scene plane from an uncalibrated perspective image under the assumption that the scene is coated with a homogeneous (but unknown) texture. We make the following novel contributions: first, we show that the problem is equivalent to estimating the vanishing line of the plane; second, we show that estimating the two degrees of freedom of this line can be decomposed into two searches each for one parameter; third, we give an algorithm for this estimation which is applicable to both regular and irregular textures. The algorithms do not require that texels are identified explicitly. But once the plane vanishing line has been obtained, then texels locations can be determined, and the geometry of the scene plane computed up to an affine transformation. We give examples of these computations on real images.